PENGARUH PERSEPSI KEADILAN DALAM KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Pada Karyawan PT.Telkom Indonesia Witel Jatim SelatanMalang) - Utari, Nyla Myrda; Azzuhri, Misbahuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aimed to observe the influence of perception of equity in compensation which consists of the aspects are external equity, internal equity, individual equity, and procedural equity that influence employee job satisfaction in PT. Telkom Indonesia Witel Jatim Selatan Malang. This kind of research is explanatory research. Data were obtain using a questionnaire. The sample in this research is 64 peoples were determined by Slovin method. The result showed are: (1) Perception of equity in compensation is directly significant positive effect on job satisfaction, (2) external equity have a significant effect on job satisfaction, (3)internal equity haven’t a significant effect on job satisfaction, (4) individual equity have a significant effect on job satisfaction, (5) procedural equity have a significant effect on job satisfaction. Keywords: perception of equity in compensation, external equity, internal equity, individual equity, procedural equity, job satisfaction